CLAY MINERALS FORMED DURING PROPYLITIC ALTERATION OF A GRANITE AND THEIR INFLUENCE ON PRIMARY POROSITY: A MULTI-SCALE APPROACH - Cassiaux M.; Proust D.; Siitari-kauppi M.; Sardini P.; Leutsch Y. (My University, 2006)
The porosity of a propylitized granite from Charroux (France), with no fractures or sealed fractures, increases by more than four times from the unaltered (0.3%) to the altered rock (1.4%). This evolution results from several local porosity modifications which occur at different scales in the rock: (1) at the core scale, from 10−1 to 10−5 m, where rock porosity changes as a function of rock-forming mineralogical composition; (2) at the mineral scale, from 10−3 to 10−7 m, where porosity depends both on the nature of the rock-forming mineral and its clay mineral alteration. Mineralogical and porosity data collected from the granite using a mineralogical map (after chemical staining and scanning electron microscopy images combined with autoradiographs) indicate that (1) the ferromagnesian rock-forming minerals — biotite and magnesiohornblende — act as the main porosity source in the unaltered granite, and (2) the nature of the clay minerals replacing rock-forming minerals in the altered granite appears to control the porosity value through two major alteration processes: chloritization and phengitization which affect the ferromagnesian minerals and produce non-porous chloritic and porous phengitic areas, respectively, at the studied scales. The observation that incipient porosity formation in granites is strongly linked to the pathway of ferromagnesian silicate alteration and subsequent clay mineral formation underlines the need to study parent-rock texture and mineralogy and their effects on subsequent near-surface weathering of granites.
Keywords: AUTORADIOGRAPH; CONNECTED POROSITY; GRANITE; MICROPROBE ANALYSIS; PROPYLITIC ALTERATION; SEM; XRD